Safer Healthcare: Strategies for the Real World (2016)
Healthcare has brought us extraordinary benefi ts, but every encounter and every treatment also carries risk of various kinds. The known risks from specifi c treatments are well established and routinely discussed by clinicians. Yet we also face risks from failures in the healthcare system, some specifi c to each setting and others from poor coordination of care across settings. For us, as patients, healthcare provides an extraordinary mixture of wonderful achievements and humanity which may be rapidly followed by serious lapses and adverse effects. Patient safety has been driven by studies of specifi c incidents in which people have been harmed by healthcare. Eliminating these distressing, sometimes tragic, events remains a priority, but this ambition does not really capture the challenges before us. While patient safety has brought many advances, we believe that we will have to conceptualise the enterprise differently if we are to advance further. We argue that we need to see safety through the patient’s eyes, to consider how safety is managed in different contexts and to develop a wider strategic and practical vision in which patient safety is recast as the management of risk over time. The title may seem curious. Why ‘strategies for the real world’? The reason is that as we developed these ideas we came to realise that almost all current safety initiatives are either attempts to improve the reliability of clinical processes or wider system improvement initiatives. We refer to these as ‘optimising strategies’, and they are important and valuable initiatives. The only problem is that, for a host of reasons, it is often impossible to provide optimal care. We have very few safety strategies which are aimed at managing risk in the often complex and adverse daily working conditions of healthcare. The current strategies work well in a reasonably controlled environment, but they are in a sense idealistic. We argue in this book that they need to be complemented by strategies that are explicitly aimed at managing risk ‘in the real world’.